Analisis Pengetahuan Dan Sikap Terhadap Kepatuhan Bidan Dalam Melaksanakan Standar Asuhan Persalinan Normal Pada Pasien Inpartu - Khairat, Nur Ummul (Universitas Ivet, 2025)
Normal delivery care is a form of midwifery care that prioritizes cleanliness and safety throughout all stages of labor, from the first to the fourth stage. Maternal and neonatal mortality rates are important indicators in assessing the quality of delivery services, particularly by midwives. This study aims to determine the relationship between midwives' knowledge and attitudes with their compliance in implementing normal delivery care standards for mothers giving birth at the Pattingalloang Community Health Center, Makassar, in 2024. This study used an analytical design with an observational cross-sectional approach. The sample consisted of all 15 midwives working at the community health center. Data were collected using questionnaires and standard operating procedures for normal delivery care, then analyzed using the chi-square test. The analysis results showed no significant relationship between knowledge (p=0.371) and attitudes (p=0.57) with the level of compliance in implementing normal delivery care. Need for other strategies to improve the quality of delivery services, one of which is through more intensive education such as counseling and classes for pregnant women. In addition, it is important for pregnant women to actively seek information from trusted sources, including social media, to broaden their understanding of health.